IS ENDOSCOPIC THERAPY SAFE AND EFFICIENT IN THE TREATMENT OF LESIONS LOCATED IN THE RECTUM? - Frugis , Marcos Onofre (2024)
Introduction: Colorectal cancer is among the most common malignant neoplasms worldwide and the pre-malignant lesions that lead to its appearance are polyps in their various types. As a minimally invasive method, endoscopic resection emerges as the preferred method for focused lesions. Objective: To carry out a review verifying whether endoscopic therapy is safe and efficient in the treatment of lesions located in the rectum. Method: Narrative review collecting information published on virtual platforms (SciELO, Google Scholar, Pubmed and Scopus). Initially, a search was carried out for descriptors related to the topic, which were identified through DeCS/MeSH, namely: “colorectal cancer, adenoma, mucosectomy, dysplasia, polyp” with AND or OR search, considering the title and/or abstract. Afterwards, only those that were most similar were chosen, and the works were read in full. Results: 41 articles were evaluated. Conclusion: With the evolution of concepts and technological improvements, there is an increasing possibility of diagnosing non-polypoid or superficial lesions (superficially elevated, flat or depressed) and laterally spreading or laterally growing lesions or tumors (LST). ) that, by definition, have a diameter greater than 10 mm. Mucosectomy may be indicated for minimally invasive treatment or prevention in cases that have not yet advanced and can be cured endoscopically.